PENGARUH KUALITAS LAYANAN E-TRACKING, HARGA DAN LOKASI TERHADAP KEPUASAN PELANGGAN (STUDI KASUS PADA PT INDAH CARGO LOGISTIK CABANG SURAKARTA) - Clarrisa Asma Hanifa; Sri Hartono; Ratna Damayanti (Jurnal Akuntansi dan Pajak, 2023)
In researching this has to find out whether the Effect of E-Tracking Service Quality, Price and Location on Customer Satisfaction at PT Indah Cargo Logistik Surakarta Branch. Researchers not know the number of population. Probability and nonprobability sampling techniques are sampling methods. The number of one hundred respondents. Multiple linear regression analysis as an analytical technique. The results in research showed that e-tracking services, prices and locations had an effect on overall good customer satisfaction.